Emphysematous and Granulomatous Submucosal Rumenitis in a Feedlot Nellore Steer. - Rocha, Juliana Ferreira; Daoualibi, Yasmin; de Lorenzo, Cíntia; Pires, Ana Paula de Castro; Brito, Marilene de Farias; de Souza, Vinícius Carneiro; Malafaia, Pedro; Ubiali, Daniel Guimarães (Acta Scientiae Veterinariae, 2018)
Background: Emphysematous rumenitis is a condition characterized by gas filled bubbles or cysts in the ruminal mucosa. Although a similar pathology is reported from swine and humans, the incidence of this disease in cattle seems to be scarce. The etiology of emphysematous rumenitis is uncertain once many factors can be involved in its pathogeny, a single cause is difficult to ascertain. This lesion usually fails to display specific clinical signs; however, some degree of malabsorption and weight loss is expected. We described a case of emphysematous granulomatous submucosal rumenitis in a 2.5-yearold feedlot Nellore steer that presented reduction on daily weight gain. Case: Rumen fragments of a 2.5-year-old Nellore steer were submitted for histopathological evaluation at the Sector of Pathological Anatomy (SAP) of the Rural Federal University of Rio de Janeiro, Brazil. The specimens were part of an experimental trial to evaluate the effect of phosphorus (P) supplementation on nutrient intake, performance and P balance in fifty feedlot Nellore steers. Following a short adaptation period, in which behavioral observations were made twice daily to assess possible adverse factors, all steers were fed with balanced diet for one hundred and sixteen days. The steers were then slaughtered in order to evaluate macroscopic changes in the gastrointestinal system. Rumen and abomasum of each steer was emptied, washed with tap water and grossly examined. One steer presented ruminal lesion, while the other forty-nine did not show any ruminal injury. Throughout the experiment the affected steer showed reduction of daily weight gain; but during clinical examination no additional clinical sign was seen. At gross inspection, a reduction in the amount of muscular and adipose tissue was seen. Multiple coalescent bullous elevated structures measuring three to ten mm diameter were covering about 40% of the ruminal surface. The affected ruminal mucosa showed irregular and atrophic papillae. Rumen samples were processed routinely and stained with Hematoxylin and Eosin, Period Acid Schiff (PAS), Grocott’s Methenamine Silver (GMS), Ziehl-Neelsen (ZN), Brown-Hopps (Gram), Giemsa and Toluidine Blue (TB) stains. Additionally formalin-fixed, paraffin wax-embedded sections were stained with a primary polyclonal rabbit antibody for Escherichia coli. Histologically the submucosa was largely replaced by cyst-like enlarged lymphatic vessels filled with gaseous content and the ruminal submucosa was infiltrated by macrophages, multinucleated giant cells, eosinophils, lymphocytes and plasma cells. Special stains were negative for granules within the mast cells, fungi, acid-fast bacilli, bacteria and protozoa. E. coli was immuno-labeled only at the ruminal epithelial surface. Discussion: This paper provided a description of a rare and possible underdiagnosed condition in cattle to highlight the necessity of recognizing ruminal changes during slaughterhouse inspection. The spontaneous and extensive emphysematous rumenitis described in this paper showed histological similarities with the analogous condition documented in the small and large intestine, mesentery and mesenteric lymph node of swine. The etiology and pathogenesis of emphysematous submucosal rumenitis remain unknown. We believe that the lesion described was the reason for the decrease of weight gain of the steer; therefore it should be considered as a differential diagnosis for conditions that affect weight gain and performance of cattle. Keywords: cattle, veterinary pathology, feedlot, emphysema, rumen.